1993
DOI: 10.1136/thx.48.7.708
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and follow up of patients prescribed long term oxygen treatment.

Abstract: Background-Prescription and use of long term oxygen treatment were audited in a large group of patients after more than five years of use of the guidelines for its prescription. Methods-Patients with a concentrator were interviewed at home with a structured questionnaire in three family health service authorities in East London. Stable oxygen saturation (Sao,) breathing air and oxygen, forced expiratory volume in one second (FEV,)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
1
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 11 publications
1
51
1
4
Order By: Relevance
“…(10). In low-income countries, higher costs resulting from electricity consumption by concentrators can be an additional problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10). In low-income countries, higher costs resulting from electricity consumption by concentrators can be an additional problem.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been associated with financial problems related to electricity consumption when concentrators are used. (9,10) Few studies have evaluated the impact of oxygen delivery systems on HRQoL in patients with chronic obstructive pulmonary disease. (11,12) Andersson et al (11) showed that HRQoL improved in patients receiving liquid oxygen treatment and deteriorated in those receiving concentrator treatment through small portable oxygen cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, this questionnaire did not discriminate between patients with different levels of hypoxia in contrast to a disease-specific measure whose scores were correlated with arterial oxygen tension Pa,O 2 [12]. It is possible that the use of an oxygen concentrator for the provision of LTOT might reduce a patients' quality of life by causing problems, such as restricted mobility, noise disturbance, and sore nose or ears from the use of nasal cannulae [14].The aim of the present study was to assess the effect of LTOT on quality of life in patients with hypoxaemia and COPD using a disease-specific measure of life quality, the St George's Respiratory Questionnaire (SGRQ) [15], as well as the SIP. Quality of life scores for the patients using LTOT were compared with scores for a control group of patients with severe COPD but without severe hypoxaemia, who therefore did not require LTOT.…”
mentioning
confidence: 99%
“…In a recent study, this questionnaire did not discriminate between patients with different levels of hypoxia in contrast to a disease-specific measure whose scores were correlated with arterial oxygen tension Pa,O 2 [12]. It is possible that the use of an oxygen concentrator for the provision of LTOT might reduce a patients' quality of life by causing problems, such as restricted mobility, noise disturbance, and sore nose or ears from the use of nasal cannulae [14].…”
mentioning
confidence: 99%
“…Several factors can be associated with muscle wasting in individuals with COPD, such as nutritional alterations, use of corticosteroids and disuse [2,3]. The pulmonary and systemic manifestations of COPD together result in a reduction of exercise capacity and development of symptoms commonly reported by patients, such as dyspnea and fatigue [4]. These symptoms are associated with a reduction in the level of physical activity in daily life and, consequently, further deterioration of exercise capacity [3,5,6].…”
mentioning
confidence: 99%